Using Qualitative Research to Assess Teaching and Learning in Technology‐Infused TILE Classrooms. (March 2014) - Van Horne, Sam; Murniati, Cecilia Titiek; Saichaie, Kem; Jesse, Maggie; Florman, Jean C.; Ingram, Beth F.
Abstract : This chapter describes the results of an assessment project whose purpose was to improve the faculty‐development program for instructors who teach in technology‐infused TILE (Transform, Interact, Learn, Engage) classrooms at the University of Iowa. Qualitative research methods were critical for (1) learning about how students and instructors interacted in these new learning spaces and (2) improving faculty development to ensure that instructors could design and implement effective learning activities in the TILE environment.